Global Monitoring Report 2014/2015 : Ending Poverty and Sharing Prosperity - World Bank Group; International Monetary Fund (Washington, DC: World Bank Group, 2014)
The Global Monitoring Report 2014/2015 will, for the first time, monitor and report on the World Bank Group’s twin goals of ending extreme poverty by 2030 and boosting shared prosperity, while continuing to track progress toward the Millennium Development Goals (MDGs).